2010
DOI: 10.1371/journal.pone.0013915
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteomic Analysis of Human Serological Antibody Responses to Vaccination with Whole-Cell Pertussis Vaccine (WCV)

Abstract: BackgroundPertussis (whooping cough) caused by Bordetella pertussis (B.p), continues to be a serious public health threat. Vaccination is the most economical and effective strategy for preventing and controlling pertussis. However, few systematic investigations of actual human immune responses to pertussis vaccines have been performed. Therefore, we utilized a combination of two-dimensional electrophoresis (2-DE), immunoblotting, and mass spectrometry to reveal the entire antigenic proteome of whole-cell pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 86 publications
1
20
1
6
Order By: Relevance
“…Several major Bp Ag (s) were identified including pertactin, filamentous hemagglutinin, and adenylate cyclase toxin. Previously, researchers have used 2D-GE, immunoblotting, and MS to identify immunoproteins of Bp [3][4][5][6][7]. Using our strategy, we identified many of the same proteins further validating and demonstrating the usefulness of this approach (see proteins with superscript in Table 1).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Several major Bp Ag (s) were identified including pertactin, filamentous hemagglutinin, and adenylate cyclase toxin. Previously, researchers have used 2D-GE, immunoblotting, and MS to identify immunoproteins of Bp [3][4][5][6][7]. Using our strategy, we identified many of the same proteins further validating and demonstrating the usefulness of this approach (see proteins with superscript in Table 1).…”
supporting
confidence: 56%
“…Their potential as candidate diagnostics, biomedical therapeutics, pathogenic markers and vaccines is an on-going subject of investigation within academia and pharmaceutical companies. Traditional strategies of identifying these important antigens (Ag) (s) usually involve a series of sodium dodecyl sulfate polyacrylamide 1-or 2-dimensional gel electrophoresis (SDS-PAGE 1D/2D-GE), immunoblotting, followed by mass spectrometry (MS) [1][2][3][4][5][6][7]. These procedures are time-consuming, laborious, and results are challenging to reproduce.…”
mentioning
confidence: 99%
“…[37][38][39] This protein is also found to be recognized by the human immune system and identified as human immunoreactive proteins of B. pertussis. 40 Since this antigen could not be sourced, direct assessment of antibody production and protective effect of the antigen were not possible. However, although the precise role of sphB1 in pertussis immune response and protection deserve further investigation, it cannot be ruled out that it may serve as one of the possible explanations for the observed differences in protection between S2 and S3.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Finn et al (1995) showed that the absence of OmpQ does not affect the capacity of B. pertussis to colonize mouse lung tissue, discarding the possibility that this protein may play a role in the survival of the bacterium inside the host. On the other hand, recent proteomic studies proposed OmpQ as a novel protective antigen candidate (de Gouw et al, 2014;Packard et al, 2004;Tefon et al, 2011;Williamson et al, 2012;Zhu et al, 2010) and even suggested that OmpQ could play a role in the pathogenesis of Bordetella (Tefon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the first studies of OmpQ, Finn et al (1995) reported that the absence of this protein did not affect the ability of B. pertussis 18323 to survive in the mouse respiratory tract. However, more recently, several reports have recognized OmpQ as an immunodominant antigen and, moreover, as a potential novel protective antigen (de Gouw Packard et al, 2004;Tefon et al, 2011;Williamson et al, 2012;Zhu et al, 2010). In addition, it has been proposed that OmpQ should play a role in the pathogenesis of Bordetella, perhaps during the first steps of infection or in the establishment of a carrier state (Tefon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%